Conflitos socioambientais na área de proteção ambiental do litoral sul em Estância/SE - Oliveira, Fagner Santos de (2020)
The Environmental Protection Area (APA) South Coast of Sergipe encompasses the entire coastline of the municipality of Estância. It is a Conservation Unit (UC) for Sustainable Use, in which there are coastal fauna and flora species, as well as dunes, lagoon outcrops and the mouth of the Rio Real. From its historical occupation process in 1575 until today, this area has undergone continuous transformations resulting from anthropic actions, which in itself justifies its choice as the object of this dissertation, since it is a UC established in an area of colonization ancient, that is, marked by the action of man over more than four hundred years. In addition, many of the existing Socio-Environmental Conflicts result from the ignorance, on the part of the actors involved, of what and what purpose an APA has; associated with the negligence of the public power to carry out local inspection actions. The present study, therefore, has as its object, the APA Litoral Sul de Sergipe, which runs through the coastal strip of the municipality of Estância/SE and has the general objective of analyzing socio-environmental conflicts there. The hypothetical-deductive method was adopted for the scope of the work, as well as the diagnostic and literary-analytical categorization methodology of Socio-environmental Conflicts by Paul Little (2001), in a quali-quantitative approach. Regarding the methodological procedures, they took place in three stages: theoretical foundation; information gathering; and analysis of them. In the theoretical basis, a consistent bibliographic research was carried out to support the study. Subsequently, information was collected, through on-site visits, georeferenced photography, satellite images, and interviews and semi-structured questionnaires were applied to the main actors involved in the conflicts. Finally, the information was analyzed and a map of socio-environmental conflicts was prepared, according to the GESTA/UFMG model (Study Group on Environmental Thematic at the Federal University of Minas Gerais), through the QGis 2.18 program. These procedures provided the necessary support for the achievement of the desired objectives, since, through the final analysis of the data, an increase in Socio-environmental conflicts in this area was found, resulting not only from the lack of knowledge of the nature and attributions of a UC and an APA, but also from market, tourist and business interests, among others; which generate a constant tension in the balance and conservation of its biodiversity. The Socioenvironmental Conflicts currently found in the APA have been categorized into three types: around the control of natural resources, around the environmental and social impacts generated by human and natural action, and around the use of environmental knowledge, identifying its actors in dispute and the disputed asset. These results can be used as subsidies for the reading of the Social and Environmental Conflicts existing in the APA, in view of the search for effective actions in favor of the sustainable use of its natural resources.